Peningkatan Keterampilan Menyimak melalui Metode Bercerita pada Pembelajaran Bahasa Indonesia Oleh Siswa Kelas XI SMK Negeri 2 Padangsidimpuan - Pulungan, Leni Oktavia; Hasibuan, Nikmah Sari; Lubis, Khatib; Harahap, Eli Marlina (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to improve students' listening skills through the application of the storytelling method in Indonesian language learning. Listening is a fundamental skill in language acquisition but often receives less attention in the learning process. This research used a Classroom Action Research (CAR) approach, consisting of two cycles. The research subjects were 32 students of class XI DPIB 1 at SMK Negeri 2 Padangsidimpuan. Data were collected through observation, tests, and questionnaires, and analyzed quantitatively using descriptive statistics. The results showed a significant improvement in both student performance and classroom engagement. In Cycle I, only 46.8% of students achieved the excellent category, which increased to 59.375% in Cycle II. Student learning activity also improved from 57.05% to 86.65%. These findings indicate that the storytelling method is effective in enhancing students' listening skills.